CHEMICAL COMPOUNDS AND ANTIOXIDANT CONTENTS OF CLOVES LEAVES ESSENTIAL OIL - Muhammad Tahir; Siti Chuzaemi; Eko Widodo; Hafsah Hafsah (Universitas Tadulako, 2020)
Essential oils from the distillation of clove leaves could act as anti-bacterial and anti-fungal agentsforeither food or feed. The purpose of this study was to identify chemical compounds and antioxidant content of clove leaves essential oils. The material used was clove leaves essential oil obtained by soxlet extraction. Clove leaves were taken from trees of over 10 years old in Palu, Central Sulawesi. Chemical compounds of the sample were analyzed by GC-MS method. Each peak that appeared on the chromatogram was identified by comparing to the standard. While the antioxidant analysis was carried out by using the DPPH (IC50) of spectrophotometry method. The results showed that the total essential oils content of clove leaves was 3,957% and there were 6 chemical compounds identified, i.e. caryophyllen (0,96%); phenol, 2-methoxy (guaiacol) (4,16%); phenol,2-methoxy-4-methyl (9.79%); phenol, 4-ethyl-2-methoxy (1.5%); phenol 2-methoxy-4-propyl (3.87%); phenol, 2-methoxy-4-(2-prophenyl) andEugenol (79.72%). While the results of antioxidant identification based on DPPH and IC50 values before purification were 0.597 and 74.358, and the respective values after purification were 0.597 and 42.255. In conclusion, the antioxidant content of clove leaves essential oils after purification is higher than before purification and it contains 3.957% essential oil.